Millie: Best Friends Dog Tales #3 - Hoyle, McCall; Keele, Kevin (Salt Lake City, Utah : Shadow Mountain Publishing, 2024)
A street dog named Millie and a young girl, who are both dealing with abandonment issues, give trust and belonging a second chance.
new kids book 2024 spring.
Ages 8-11.
Grades 4-6.
Keywords: Trust -- Fiction; Belonging -- Fiction; JUVENILE FICTION / Social Themes / Emotions & Feelings; JUVENILE FICTION / Animals / Dogs; Emotional support animals; Dogs -- Fiction